High-throughput phenotyping of wheat root angle and coleoptile length at different temperatures using 3D-printed equipment - Nevzat Aydin; Mesut Ersin Sönmez; Tuğba Güleç; Bedrettin Demir; Hadi Alipour; Aras Türkoğlu (BMC Plant Biology)
Abstract Background Innovation in crop establishment is crucial for wheat productivity in drought-prone climates. Seedling establishment, the first stage of crop productivity, relies heavily on root and coleoptile system architecture for effective soil water and nutrient acquisition, particularly in regions practicing deep planting. Root phenotyping methods that quickly determine coleoptile lengths are vital for breeding studies. Traditionally, direct selection for root and coleoptile traits has been limited by the lack of suitable phenotyping methods, genetic and phenotypic complexity, and poor repeatability in sampling. In this study, we innovated a method utilizing 3D printing technology to measure root angle and coleoptile length in wheat seedlings. We evaluated seedlings from eight different wheat genotypes across varying temperatures and validated our findings through image processing techniques. Results The analysis of variance in root architecture revealed significant differences among genotypes for root angle. Temperature treatments also significantly influenced shoot length, number of roots and total root length. The Tosunbey genotypes exhibited the highest root angle and the lowest root angle was observed in Altindane genotypes. Additionally, we observed that increasing the temperature led to an increase in seedling root length. Similarly, the coleoptile architecture analysis showed significant differences among genotypes in coleoptile length, leaf length, number of roots, and total root length. Temperature treatments and deep sowing applications significantly affected these traits as well. The Tosunbey and Müfitbey genotypes exhibited the longest coleoptile length, whereas the Nevzatbey genotype showed the shortest. Conclusion Selecting for a narrow root angle and a high number of seminal roots can result in deeper, more branched root systems. Furthermore, developing wheat genotypes with longer coleoptiles can enhance plant production and early vigor, particularly with deep sowing. Our method, using the eqiupments producing by 3D printing technology enables high-throughput phenotyping of wheat roots and coleoptiles, offering new insights into root and coleoptile system regulation at different temperature conditions. This method can be seamlessly integrated into breeding programs to enhance drought tolerance, rapidly phenotyping populations for root and coleoptile characteristics.